Interleukin-34 Synovial Fluid Was Associated with Knee Osteoarthritis Severity: A Cross-Sectional Study in Knee Osteoarthritis Patients in Different Radiographic Stages. (12th August 2018) - Wang, Shuang-Lei; Zhang, Rui; Hu, Kong-Zu; Li, Mao-Qiang; Li, Zhan-Chun
Abstract : Background . Inflammation might play a crucial role in the pathogenesis of osteoarthritis (OA). Interleukin-34 (IL-34) is a well-known proinflammatory cytokine. Objective . The objective of this study was to detect IL-34 levels in serum and synovial fluid (SF) of patients with OA and to investigate their correlation with radiographic and symptomatic severity. Methods . One hundred and eighty-two OA patients and 69 controls were recruited. IL-34 levels were measured by enzyme-linked immunosorbent assay (ELISA). Radiographic and symptomatic severity of OA was reflected by Kellgren-Lawrence (KL) grades and Western Ontario McMaster University Osteoarthritis Index (WOMAC) scores, respectively. Results . SF IL-34 levels were independently associated with the KL grade (B = 0.273, 95% CI: 0.150–0.395;P < 0.001 ). SF IL-34 levels were significantly correlated with WOMAC scores (r = 0.265, 95% CI: 0.123–0.399;P < 0.001 ). The correlation between SF IL-34 levels and WOMAC scores was still significant after adjusting for confounding factors (B = 0.020, 95% CI: 0.001–0.038;P = 0.035 ) in OA patients. Conclusions . We found that IL-34 levels in SF were significantly associated with the radiographic and symptomatic severity of knee OA.